Wild chamomile essential oils bioactivity at different locations in sulaimani region, Iraq - Ahmed, Rozhgar Mustafa; Ali , Miran Khalil; Mahmood, Banaz Jamal (Journal of Kerbala for Agricultural Sciences, 2024)
This study was conducted to evaluate the bioactivity of wild chamomile (Matricaria chamomile L.), in response to different elevations flower samples at full blooming. The analysis of chamomile flower essential oils (EOs) through GC-MS identified the predominant abundance of terpenoids including Bisabolol oxides, farnesene, and Azulen, constituting 61.765% of the identified compounds across various locations. The highest concentration was 74.554% out of the total components observed at Kanipanka, while it was the minimum (16.414%) at the Qaradagh location. Oppositely the highest concentration of Farnasene was observed at the Qaradagh location, while the lowest concentration occurred with the essential oil of Kanipanka.α-Bisabolol oxide A% dominates, except in the Qara Dagh location. The best antioxidant concentration was found in Sharbazher essential oil. The essential oil in Sharbazher significantly shows the highest inhibition capacity (IC%). The stronger IC50% value was 64.645 µg mL-1, recorded at the Qara Dagh location. The disc diffusion assay revealed that the activity of chamomile essential oil at various locations significantly affected the death of most bacterial strains (Gram-negative and Gram-positive). Chamomile EOs from the Kanipanka location recorded maximum antibacterial activity on Pseudomonas aeruginosaPenjween EOs observed the maximum antibacterial activity against Staphylococcus haemolyticus, while a high level inhibition zone (IZ) against Enterococcus faecalis was observed in Bakrajo. The finding revealed that the highest MIC and MBC against Pseudomonas aeruginosa were achieved with the concentration of 2.5 µg mL-1 of Kanipanka EOs.